2009
DOI: 10.2319/070308-341.1
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Bone Loss around Incisors in Surgical Skeletal Class III Patients

Abstract: Objective: To test the hypothesis that there is no difference in the vertical alveolar bone levels and alveolar bone thickness around the maxillary and mandibular central incisors in surgically treated skeletal Class III malocclusion patients. Materials and Methods:The study sample comprised 20 Korean patients with skeletal Class III malocclusion with anterior crossbite and openbite (9 male, 11 female, mean ages 24.1). Threedimensional cone beam computed tomography images were taken at least 1 month before the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 25 publications
4
79
1
21
Order By: Relevance
“…It is evident that the significantly reduced vertical height and horizontal thickness explains the risks of periodontal problems. 15 In our study, the lingual alveolar bone losses showed no difference between the early-treated and later-treated groups. As to the labial side, the AC was higher at 3.30 mm 6 1.18 mm (Table 4) in the later-treated group.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is evident that the significantly reduced vertical height and horizontal thickness explains the risks of periodontal problems. 15 In our study, the lingual alveolar bone losses showed no difference between the early-treated and later-treated groups. As to the labial side, the AC was higher at 3.30 mm 6 1.18 mm (Table 4) in the later-treated group.…”
Section: Discussionmentioning
confidence: 62%
“…Reference points, lines, and measurement variables are described in Figure 5 and Tables 1 and 2. The measurement methods were revised from Kim et al 15 and followed the same methods as reported in our previous study 3 when measuring a nonuniform root shape. Sagittal slices were evaluated where the maxillary central incisor showed the widest labiolingually in the axial view.…”
Section: Methodsmentioning
confidence: 99%
“…6,8,[14][15][16] In the study of Kim et al, vertical alveolar bone levels and alveolar bone thickness were compared between lower and upper incisors in surgical skeletal class III patients; they found that the amount of bone loss at the lower incisors was greater than that of the uppers, and lingual bone thickness was greater at the upper incisors and smaller at the opposing teeth. 17 When Baysal et al compared alveolar bone thickness between skeletal class I and II malocclusions, the observations were that buccal alveolar bone thicknesses in class I patients were significantly greater than those in class II patients, and that the buccal apical alveolar bone thickness was greater than lingual in class II malocclusions. 18 Earlier studies about the density of the lower alveolar bone were made with the help of pyknometry, microradiography or histoquantification.…”
Section: Jcdpmentioning
confidence: 99%
“…Edwards (1976) and Hwang and Moon (2001) reported the limitation of alveolar bone modeling and remodeling during retraction and intrusion of maxillary incisors. Kim Y. et al (2009) evaluated alveolar bone loss around incisors in surgical skeletal Class III patients, and Nelson and Artun (1997) showed the relationship between age and alveolar bone loss. Wehrbein et al (1995) and Evangelista et al (2010) appraised the prevalence of alveolar bone dehiscence in untreated patients and subjects who have undergone tooth retraction.…”
Section: Introductionmentioning
confidence: 99%